2014
DOI: 10.2135/cropsci2013.09.0601
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Linkage Disequilibrium, and Genome Evolution in Soft Winter Wheat

Abstract: Understanding genetic diversity within a breeding population is fundamental to its efficient exploitation. The advent of new high‐throughput marker systems offers the opportunity to expand the scope and depth of our investigation of diversity. Our objective was to analyze the genetic diversity of two populations of soft winter wheat (SW) adapted to the eastern United States. The historical population (HP) consisted of 187 lines released or developed from 1808 to 2005. The elite population (EP) consisted of 449… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 60 publications
4
19
1
Order By: Relevance
“…Results from association analysis using both models (Q + K and PCs + K) were very consistent despite showing small differences in the significant level, therefore we report on the results from Q + K model as it most likely represent better the population structure previously described for this population (Cabrera et al 2014). In our association analysis of 583 DArTs and 10 gene-based markers, significant associations at family-wise significant level or false discovery rate (FDR) were not detected.…”
Section: Association Analysis In a Diversity Panelsupporting
confidence: 56%
See 3 more Smart Citations
“…Results from association analysis using both models (Q + K and PCs + K) were very consistent despite showing small differences in the significant level, therefore we report on the results from Q + K model as it most likely represent better the population structure previously described for this population (Cabrera et al 2014). In our association analysis of 583 DArTs and 10 gene-based markers, significant associations at family-wise significant level or false discovery rate (FDR) were not detected.…”
Section: Association Analysis In a Diversity Panelsupporting
confidence: 56%
“…We integrated the mapping of quality traits in a diversity panel of 187 lines selected as described by Souza et al (2012) and characterized by Cabrera et al (2014); and five soft red winter wheat (SRWW) bi-parental populations ( Table 1). The results obtained were compared to published results (Smith et al 2011).…”
Section: Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The population contained multiple lines from the same cross and full sibs and half sibs clustered together. When the structure of this population was analyzed by Cabrera et al (2014), population stratification suggested up to six groups. The six groups were mainly distinguished based on differential parentage from the following key parents: VA98W‐706, P.961341A3‐2‐2, P.92145E8‐7‐7‐1‐9, ‘Roane’, ‘Patton’, ‘Honey’, and OH751 (Cabrera et al, 2014).…”
Section: Resultsmentioning
confidence: 99%